Meaning of the Messages and Values in the Lyrics of the Toluni Dance Song for Welcoming, Weddings and Circumcisions in the Banggai Islands Region - Sri Sulistiawati Lalu; Asna Ntelu; Ayu Hidayanti Ali (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the meaning of messages and values contained in the lyrics of Toluni Dance across three traditional ceremonies of the Banggai Archipelago community: guest welcoming ceremonies, weddings (Toluni Osoan), and circumcision ceremonies (Toluni Monsunat). Toluni Dance is a local cultural heritage whose lyrics function as a medium for communication, advice, prayer, and the transmission of life values. The study employs a semantic approach with a descriptive qualitative method. Data in the form of words, phrases, and sentences within the lyrics were collected through listening-note-taking techniques and documentation from performance videos and manuscripts in three villages: Montomisan, Lolantang, and Bulagi. The findings reveal that the meanings embedded in the Toluni Dance lyrics include emotional meaning (respect, hope, affection), symbolic meaning (life journey, communal prayer, spiritual transition), and connotative meaning (aspirations, advice, religious commands). The identified values encompass cultural values (preserving dance tradition as identity), social values (solidarity, mutual love, communal prayer), religious values (Islamic sharia, God’s commands, blessings), aesthetic values (phrase repetition, metaphors, rhythm), and moral values (honesty, loyalty, filial piety). The three ceremonial contexts demonstrate a dynamic shift in meaning and function: from social aspiration (welcoming ceremony), to household education (wedding ceremony), to faith reinforcement (circumcision ceremony). This study confirms that the lyrics of Toluni Dance are not merely dance accompaniments but rather a medium for transmitting noble values relevant to the preservation of local culture.